Vitamin D receptor ApaI polymorphism associated with progression of liver disease in Vietnamese patients chronically infected with hepatitis B virus - Nghiem Xuan Hoan; Nguyen Khuyen; Dao Phuong Giang; Mai Thanh Binh; Nguyen Linh Toan; Do Tuan Anh; Ngo Tat Trung; Mai Hong Bang; Christian G. Meyer; Thirumalaisamy P. Velavan; Le Huu Song (BMC, 2019)
Abstract Background Vitamin D derivatives and their receptor (VDR) are potent modulators of immune responses in various diseases including malignancies as well as in metabolic and infectious disorders. The impact of vitamin D receptor polymorphisms on clinical outcomes of hepatitis B virus (HBV) infection is not well understood. This study aims to investigate the potential role of VDR polymorphisms (TaqI, FokI, ApaI, and BsmI) in Vietnamese HBV infected patients and to correlate these polymorphisms with the progression of HBV-related liver disease. Methods Four hundred forty-three HBV infected patients of the three clinically well-defined subgroups chronic hepatitis B (CHB, n = 183), liver cirrhosis (LC, n = 89) and hepatocellular carcinoma (HCC, n = 171) and 238 healthy individuals (HC) were enrolled. VDR polymorphisms were genotyped by DNA sequencing and in-house validated ARMS assays. Logistic regression models were applied in order to determine the association of VDR polymorphisms with manifest HBV infection as well as with progression of related liver diseases mulin different genetic models. Results The VDR ApaI CA genotype was less frequent in HCC than in CHB patients in different genetic models (codominant model, OR = 0.5, 95%CI = 0.3-0.84, P = 0.004; dominant model, OR = 0.46, 95%CI = 0.27-0.76, P = 0.0023). In the recessive model, the genotype ApaI AA was found more frequently among HCC compared to CHB patients (OR = 2.56, 95%CI = 1.01-6.48, P = 0.04). Similarly, the ApaI CA genotype was less frequent in HCC than in non-HCC group codominant model, OR = 0.6, 95%CI = 0.4-0.98, dominant model, P = 0.04 and OR = 0.6, 95%CI = 0.38-0.90, P = 0.017). The ApaI genotypes CA and AA was significantly associated with higher levels of liver enzymes, bilirubin, and HBV DNA (P < 0.05). No association between TaqI, FokI and BsmI polymorphisms and any clinical outcome as well as liver disease progression was found. Conclusions Among the four investigated VDR polymorphisms, ApaI is associated with clinical outcome and liver disease progression in Vietnamese HBV infected patients.